2020
DOI: 10.1111/sode.12481
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and prosocial behaviors: A meta‐analysis

Abstract: Ascertaining whether and the extent to which different aspects of parenting are associated with prosocial behaviors could inform parenting programs in cultivating healthy development. Multilevel meta-analyses (k = 124) involving children and adolescents were conducted to examine associations between parenting and prosocial behaviors while accounting for demographic and study characteristics. Authoritative parenting (r = .174, p < .001) was associated positively whereas authoritarian parenting (r = −.107, p < .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 158 publications
(116 reference statements)
3
52
0
Order By: Relevance
“…One possibility is that supportive parenting may not be enough by itself to predict Nicaraguan adolescents' prosocial behaviors through these hypothesized mediators. This is consistent with the conclusions of a recent meta-analytic review that showed that warm, supportive, and responsive parenting practices were not strongly linked to several forms of prosocial behaviors, and some studies yielded nonsignificant links (Wong et al, 2020). In future research, it might be important to consider interactions between supportive and strict parenting in predicting Nicaraguan adolescents' prosocial behaviors because these parenting practices accompany each other and are seen as relatively normative in Latinx cultures (Halgunseth et al, 2006).…”
Section: Indirect Effects Of Parenting On Prosocial Behaviorssupporting
confidence: 86%
See 1 more Smart Citation
“…One possibility is that supportive parenting may not be enough by itself to predict Nicaraguan adolescents' prosocial behaviors through these hypothesized mediators. This is consistent with the conclusions of a recent meta-analytic review that showed that warm, supportive, and responsive parenting practices were not strongly linked to several forms of prosocial behaviors, and some studies yielded nonsignificant links (Wong et al, 2020). In future research, it might be important to consider interactions between supportive and strict parenting in predicting Nicaraguan adolescents' prosocial behaviors because these parenting practices accompany each other and are seen as relatively normative in Latinx cultures (Halgunseth et al, 2006).…”
Section: Indirect Effects Of Parenting On Prosocial Behaviorssupporting
confidence: 86%
“…Moreover, scholars have noted the positive social development consequences of parents who are moderately demanding (Grusec & Goodnow, 1994;Maccoby & Martin, 1983). Nonetheless, the complex pattern of relations between both supportive and strict parenting practices and specific forms of prosocial behaviors could help explain why sometimes parenting is weakly or nonsignificantly related to prosocial behaviors in prior studies (see Wong et al, 2020). Future research is warranted to further investigate the parenting correlates of specific forms of prosocial behaviors and in studies of native-residing Latin American parents and adolescents.…”
Section: Direct Effects Among Parenting Prosocial Moral Reasoning Familism and Prosocial Behaviorsmentioning
confidence: 98%
“…Psychological controlling practices include withdrawing love, inducing guilt, shaming, and invalidating the child's perspective (Barber et al, 2005). Previous studies have consistently shown that parental psychological control is related to lower academic achievement, more externalizing and internalizing symptoms, and fewer prosocial behaviors (e.g., Pinquart, 2017;Wong et al, 2021). Lastly, parental conditional regard (PCR) is the practice through which parents show love and appreciation when children fulfill their parental expectations (Assor et al, 2014).…”
Section: Parenting Dimensions From a Self-determination Perspective And Their Effectsmentioning
confidence: 99%
“…This association is unexpected, as prior work typically found either positive associations or no associations between parental warmth and children's prosociality (Hastings et al, 2015). Because warmth is one component of a permissive parenting style (together with little and inconsistent limit setting; Baumrind, 1971), one possibility is that for some mothers, warmth may be accompanied by indulgence, with this permissive style linked in turn to lower prosociality (Wong et al, 2021). We therefore included both permissive parenting and authoritative parenting (which combines warmth with consistent, effective limit setting) as control variables in the next two studies.…”
Section: Examining Religiosity As a Moderatormentioning
confidence: 99%